Immune microenvironment features and efficacy of PD‐1/PD‐L1 blockade in non‐small cell lung cancer patients with EGFR or HER2 exon 20 insertions. Issue 2 (18th November 2020) - Chen, Kaiyan; Pan, Guoqiang; Cheng, Guoping; Zhang, Fanrong; Xu, Yanjun; Huang, Zhiyu; Fan, Yun
Abstract : Background: Insertions in exon 20 (Ex20ins) of epidermal growth factor receptor ( EGFR ) and human epidermal growth factor receptor 2 ( HER2) are relatively insensitive to first‐ and second‐generation EGFR‐tyrosine kinase inhibitors (TKIs) in non‐small cell lung cancer (NSCLC). This study aimed to investigate the immune microenvironment features and efficacy of PD‐1/PD‐L1 blockade of NSCLC with EGFR and HER2 Ex20ins. Methods: Clinical characteristics, coexisting mutations, and outcomes to EGFR‐TKIs and immune checkpoint blockade were reviewed for NSCLC patients with exon 20 mutations of EGFR or HER2 . Data obtained included the molecular spectrum (extended genotyping for mutations in 324 cancer‐related genes), as well as tumor mutational burden (TMB), PD‐L1 protein expression, and the abundance of CD4+ and CD8+ tumor‐infiltrating lymphocytes (TILs). Results: A total of 1270 NSCLC patients were identified. Of these, 504 (39.7%) cases had EGFR mutations and 6.9% (35/504) of them had EGFR Ex20ins. Meanwhile, 21 (1.7%) cases with HER2 Ex20ins were detected. Comprehensive genomic profiling identified A767_V769dup variant (25.0%) was the most common type in tumors with EGFR Ex20ins. Co‐occurring mutations were not uncommon including TP53 (45%), PIK3CA (20%), CDKN2A (10%), and EGFR amplification (20%). The average TMB was 3.3 mutations/megabase. PD‐L1 expression in patients with EGFR Ex20ins was significantly higher than for those with HER2 mutations (48.6% vs. 19.0%, P = 0.027). High TMB and PD‐L1 expression was independently associated with significantly poor prognosis ( P = 0.025, P = 0.045, respectively) while there was no association between CD4+/CD8+ TILs and prognosis in EGFR or HER2 mutant NSCLC. Finally, patients harboring EGFR Ex20ins seemed to be sensitive to PD‐1/PD‐L1 blockage whereas it showed limited efficacy in patients with HER2 Ex20ins. Conclusions: NSCLC patients with EGFR / HER2 Ex20ins had similar genomic characteristics and distinct immune features. Patients with EGFR Ex20ins had significantly higher PD‐L1 expression than those with HER2 mutations, which may be the potential reason for the different responses to PD‐1/PD‐L1 blockage. Abstract : NSCLC patients with EGFR/HER2 Ex20ins had similar genomic characteristics and distinct immune features when compared to common EGFR mutations. Patients with EGFR Ex20ins had significantly higher PD‐L1 expression than those with HER2 mutations, which may be the potential reason for the different responses to PD‐1/PD‐L1 blockage.